Evaluación de cuatro extractos vegetales a tres dosis para el control de bactericera cockerelli en condiciones de laboratorio. - Chicaiza Perez, Carmen Lucia (2023)
Vegetable extracts based on wild plants are used as a natural alternative for pest control. This research was carried out in the entomology laboratory of the Technical University of Cotopaxi campus Salache, with the objective of evaluating the effect of plant extracts for the control of paratrioza (Bactericera cockerelli) under controlled conditions, whose purpose was to establish which of the extracts under study showed better control of the pest and at the same time ensure that it is environmentally friendly. Within this research work, a 4 x 3 +1 factorial arrangement was used, implemented in a completely randomized block design with three replications, for which the plant extracts higuerilla, chamico, ruda and Santamaria were elaborated, then the flies were placed in glass boxes, after which the application of the extracts was carried out in three doses for each treatment which are T1 5ml, T2 10 ml, T3 15ml and a Control. Afterwards, the dead flies Bactericera cockerelli were counted and data was collected 2 hours after application. Once this process was completed, the data were entered into the statistical program Infostat which yielded the corresponding results, which were that T1 higuerilla is highly significant, while the other extracts did not give better significance, the treatment T1 higuerilla with a dose of 15 ml killed 38 flies out of 50 with an average of 0.76% efficacy, that is to say that. The extract of (higuerilla at a dose of 15 ml), showed higher mortality in adults of B. cockerelli. Therefore, it is recommended to use higuerilla extract at a dose of 15 ml to control the incidence of Bactericera cockerelli.